La novela como fuente para la historia ambiental: El caso de Sub terra en Lota - Rivera Inostroza, Diego (Historiografías, 2024)
Abstract This research explores how novels can serve as valuable sources for environmental history studies by reflecting on the interactions between humans and their environment. To demonstrate this, the work briefly reviews the history of the discipline, then justifies the utility of novels as a source for this field, and presents a historical context of the Lota commune (Chile) in the second half of the 19th century. Finally, Sub terra by Baldomero Lillo is analyzed, highlighting how the work represents life in the coal mines of Lota during the peak of the mining company. The analysis, conducted from an interdisciplinary approach that integrates literature and history, aims to understand the descriptions of the environment through some of the eight stories covered by the novel, identifying key elements of the natural environment and the relationship between the miners and this. Additionally, the concept of environment is examined, understood as the set of natural elements that manifest in the novel through the challenges of mining work and power dynamics. The research concludes that Sub terra provides an enriching understanding of the relationships between human society and the natural environment, thus complementing traditional historiographical studies. Keywords Novel, Lota, environment, Environmental history